PENGEMBANGAN KAWASAN WISATA PANTAI TAMAN BERBASIS PARIWISATA BERKELANJUTAN DI KABUPATEN PACITAN - Rendrarini, Diana; Susila, Candra Budi; Susilo, Hendro; Minarsih, Susi; Nugroho, Tri Cahyo (Jurnal Teknik Sipil dan Arsitektur, 2026)
Pantai Taman in Ngadirojo District, Pacitan Regency, possesses significant potential as a sustainable coastal tourism destination with unique geological characteristics in the form of karst cliffs, abrasion platforms, and sea turtle conservation areas. However, this potential has not been optimally managed, as indicated by fluctuating tourist visits and limited supporting facilities. This study aims to formulate a sustainable tourism development concept based on physical, environmental, social, and economic aspects. The research employs a qualitative-descriptive method with spatial and collaborative governance approaches. Data were collected through field observations, in-depth interviews with stakeholders, and document studies. The findings reveal that tourism development faces fundamental challenges, including the absence of a comprehensive masterplan, weak zoning implementation, minimal environmental management (waste and wastewater), and non-optimal community involvement. The study recommends an integrated development concept with four main strategies: (1) ecologically-based zoning with strict protection of conservation areas and sea turtle habitats; (2) environmentally friendly infrastructure development supporting waste management and clean water availability; (3) a collaborative governance model involving government, BUMDes, Pokdarwis, and local communities; (4) community economic empowerment through UMKM development and sustainable tourism packages. The implementation of this concept is expected to increase tourist visits by 15-20% per year while maintaining the environmental carrying capacity of the coastal ecosystem